Prime ends in the mapping theory on the Riemann surfaces - Ryazanov, V.I.; Volkov, S.V. (Український математичний вісник, 2017)
It is proved criteria for continuous and homeomorphic extension to the boundary of mappings with finite distortion between domains on the Riemann surfaces by prime ends of Caratheodory.